Serum 25-Hydroxyvitamin D in Patients with Major Depressive Disorder - Leila Dana-Alamdari; Sorayya Kheirouri; Seyed Gholamreza Noorazar (Tehran University of Medical Sciences, 2015)
Background: We investigated the association between serum 25(OH) D levels and depressive symptoms in patients with major depressive disorder (MDD). Methods: Eighty-five adults, 44 drug free patients with MDD and 41 apparently healthy controls, participated in the study. The Hamilton Depression Rating Scale was used to assess severity of major depression. Mental health of the controls was assessed according to DSM-IV criteria. Stress level of the participants was assessed by the Holmes and Rahe stress scale. Serum 25(OH) D levels was measured by immunochemiluminescence assay. Vitamin D deficiency was defined as a serum 25(OH) D concentration of lower than 20 ng/ml. Results: Depressed patients had the higher levels of stress. There was a positive correlation between stress level and disease severity (r= 0.32, P= 0.03). In total participants, mean percentage of vitamin D deficiency was 77.6% with 75% in patients and 80.5% in the healthy subjects. There were no differences between the two groups in serum 25(OH) D levels and percentage of subjects with the vitamin deficiency. A negative correlation was observed between disease severity and serum 25(OH) D level of patients with depression episodes < 2 y (r= -0.38, P = 0.08) and winter samples (samples collected and measured from December to march, r= -0.62, P = 0.004). Conclusion: Serum 25(OH) D levels were not associated with depression. However, the inverse relationship between levels of vitamin D and depressive symptoms in current depression episodes and in sun-deprived season warrants further investigation.